Strawberry-herb intercropping: a 2-year study toward sustainable intensification and diversification - Soppelsa, Sebastian; Gasser, Michael; Castellan, Alessia; Pramsohler, Manuel; Zago, Massimo; Matteazzi, Aldo; Kelderer, Markus (Frontiers in Sustainable Food Systems, 2025)
Intercropping is considered a biodiversity-promoting practice and consists of the simultaneous cultivation of multiple crops in the same field. Despite its ecological benefits, its adoption in specialized farming systems—such as strawberry monocultures—remains limited, as these systems typically focus on maximizing income from a single crop. The experiment investigated the effects of intercropping strawberry (Fragaria × ananassa) with herbs such as chives (Allium schoenoprasum L.), marigold (Calendula officinalis L.), peppermint (Mentha × piperita L.), strawberry mint (Mentha suaveolens Ehrh.) and common sage (Salvia officinalis L.), using a 2:1 strawberry-to-herb ratio. Conducted over two consecutive years (2021–2022) in the alpine environment of Martell Valley (South Tyrol, Italy), the study assessed plant growth, fruit production, biological and economic feasibility, and the impact of intercropping on beneficial species, including pollinators, pests, and predators. Our results showed significant year-to-year variation. Although strawberry plants intercropped with herbs in 2021 achieved a fruit production that was not significantly different from that of pure stand (on average 150 g plant−1), the intercropping systems outperformed monocropping as revealed by indices such as land equivalent ratio (LER) and income equivalent ratio (IER) both greater than one. However, in the second year of cultivation (2022), the main parameters showed a decline. For example, strawberry plant biomass was decreased (by an average of 33%) in intercropping combinations involving chives, calendula and peppermint, resulting in a reduction in strawberry production of over 50% compared to monoculture. Indeed, the interaction between different plant species analyzed with competitive indices showed that strawberry plant appeared as the dominated crop in those combinations (aggressivity for strawberry: Af < 0; competition ratio for strawberry: CRf < 1). In both years, leaf nutrient content in intercropped strawberry plants was statistically similar to that of monocropped plants. Conversely, significant differences were observed in intercropped herbs (e.g., K + 50% and S + 30% in marigold and chives leaves, respectively). Intercropping systems, especially with chives and marigold, increased the richness of arthropod species (+100% as compared to strawberry in pure crop). Our research work contributes to a better understanding of the biological and economic feasibility of intercropping as a diversified farming practice for a strawberry farm. Furthermore, our findings offer a foundation for further investigations into interspecies interactions, particularly in terms of enhancing pollinator attraction and pest repulsion.